The application of the theory of planned behavior to understand the intention of weight loss practice among overweight adolescentS - Sidek, Suriati; Ajau, D.; M.Y., Safiah (IIUM, 2016)
Introduction: Overweight adolescents have been reported to struggle in losing weight. However, their intention to engage in weight loss practice remains unclear. Therefore, the aim of this qualitative study was to understand the factors that lead to the intention of weight loss practice among overweight adolescents using the Theory of Planned Behavior (TPB).